A bridge to clean cooking? The cost-effectiveness of energy-efficient biomass stoves in rural Senegal - Gunther Bensch; Marc Jeuland; Luciane Lenz; Ousmane Ndiaye (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Rural areas of sub-Saharan Africa have experienced limited progress towards the sustainable development goal of universal access to clean cooking. Energy-efficient biomass cookstoves (EEBCs) are considered a potential bridge technology, but EEBC models vary widely, and there is a lack of understanding about their real-world use implications. We conduct a randomized controlled trial in rural Senegal to compare a low-cost, locally produced stove designed to achieve fuel savings and an expensive, imported stove shown to be more efficient and emissions-reducing in the laboratory. We find that the two EEBCs perform similarly: both reduce fuel consumption but have no significant impact on cooking time and fuel collection, emissions, or objective health measures. We conclude that the technically advanced option is not cost effective for most of our sample, while the low-cost EEBC can be seen as a stop-gap solution that primarily reduces fuel use. The findings underpin the importance of customizing EEBC dissemination to local context and baseline cooking patterns. – – In den ländlichen Gebieten Afrikas südlich der Sahara lassen sich nur begrenzte Fortschritte beim allgemeinen Zugang zu sauberem Kochen beobachten. Energieeffiziente Biomasse-Kochherde (EEBCs) gelten als potenzielle Brückentechnologie, EEBC-Modelle unterscheiden sich jedoch sehr, und es mangelt an Evidenz zu ihrer Effektivität in der Praxis. Diese Studie vergleicht einen kostengünstigen, lokal produzierten Herd, der auf Brennstoffeinsparung ausgelegt ist, mit einem teuren, importierten Herd, der sich im Labor als effizienter und emissionsmindernd erwiesen hat. Hierfür nutzen wir eine randomisierte, kontrollierte Studie unter Haushalten im ländlichen Senegal. Wir kommen zu dem Ergebnis, dass die beiden EEBCs ähnliche Effekte zeigen: Beide reduzieren den Brennstoffverbrauch, haben aber keinen signifikanten Einfluss auf die Kochzeit, die Dauer des Sammelns von Brennstoff, die Emissionen oder objektive Gesundheitsmessungen. Wir kommen zu dem Schluss, dass die technisch fortschrittlichere Option für die meisten Haushalte unserer Stichprobe nicht kosteneffizient ist, während die kostengünstige EEBC als Übergangslösung angesehen werden kann, die in erster Linie den Brennstoffverbrauch reduziert. Die Ergebnisse unterstreichen, wie wichtig es ist, die Verbreitungsstrategien von EEBCs auf den lokalen Kontext und lokale Kochgewohnheiten anzupassen.
Keywords: C93; D12; O12; O13; Q51; Q53; 330; Cookstoves; energy access; biomass burning; energy efficiency; technology choice